Предмет: Алгебра,
автор: vladozsz
2(4 - 2x) + 6 = -6x + 4. Ответьте пожалуйста!
Ответы
Автор ответа:
6
Ответ:
x = -5
Объяснение:
2(4 - 2x) + 6 = -6x + 4
8 - 4x + 6 = -6x + 4
6x - 4x = 4 - 8 - 6
2x = -10
x = -5
Автор ответа:
2
Ответ:
х=-5
Объяснение:
2(4-2х)+6=-6х+4
8-4х+6=-6х+4
-4х+6х=4-6-8
2х=-10
х=-5
Похожие вопросы
Предмет: Другие предметы,
автор: lenusika84
Предмет: Русский язык,
автор: alekspav1983
Предмет: Русский язык,
автор: phs35lt1662
Предмет: Математика,
автор: kanyakhin
Предмет: Алгебра,
автор: AliceMagic